The Relationship between Information Seeking and Treatment-Seeking Behavior in Pulmonary Tuberculosis Patients in the Service Area of Pacerakkang Community Health Center. - Jusma; Suarnianti Tawil; Eva Arna Abrar (Indonesian Journal of Nursing and Health Care, 2024)
Background: Pulmonary tuberculosis ranks third globally in terms of prevalence. This disease is caused by Mycobacterium tuberculosis, with patients whose sputum contains Mycobacterium tuberculosis serving as its contagious source. According to observations in South Sulawesi, Makassar City leads in having the highest number of TB cases, reaching 5,418 cases.Objective: This study aims to determine the relationship between information seeking and treatment-seeking behavior among pulmonary tuberculosis patients in the service area of Pacerakkang Community Health Center.Metode: Adopting a cross-sectional study design with simple random sampling technique, the research involved 52 respondents. Data collection was conducted using a questionnaire, and the collected data were processed using a master table.Results: The results of the chi-square test regarding treatment-seeking behavior with information seeking show p <0.05.Conclusion: In conclusion, there is a significant relationship between information seeking and treatment-seeking behavior among pulmonary tuberculosis patients in the service area of Pacerakkang Community Health Center